Outcomes of COVID-19 in 24 hospitalized liver transplant recipients: an observational study - Amir M. Sadeghian; Mohsenreza Mansourian; Mitra Ranjbar; Sobhan Kazemi; Marzieh Nojomi; Seyed Yahya Zarghami; Farrokhlagha Hosseini; Mohammad Hosein Mohammadi (BMC Infectious Diseases, 2024)
Abstract Background Although liver transplant (LT) recipients are considered a population at risk of severe features of coronavirus disease 2019 (COVID-19), data in this regard are scarce and controversial. In this study, we reported the outcome of 24 cases of LT recipients who were hospitalized due to COVID-19 and investigated the role-playing factors in the severity of the disease. Methods In this single-center, analytic case-series study, eligible patients were among LT recipients who were hospitalized due to the diagnosis of COVID-19 based on positive results of polymerase chain reaction. Participants were categorized as severe COVID-19 if they were admitted to the intensive care unit, experienced respiratory failure demanding mechanical ventilation, or eventually died. Demographic and clinical data, COVID-19 symptoms and specific treatments, laboratory biomarkers, and immunosuppressive regimens and their alteration during the admission were recorded. Analysis was done using SPSS software. Results Twenty-four hospitalized LT patients were included, of which nine had severe and fifteen had non-severe COVID-19. Out of 9 patients with severe COVID-19, four sadly died. The analysis and comparison between the two groups revealed longer hospital stays (P = 0.02), lower lymphocyte counts (P = 0.002), and higher levels of C-reactive protein (CRP) (P = 0.006) in patients with severe COVID-19. Patients with non-severe COVID-19 had higher doses of tacrolimus and mycophenolate in their baseline immunosuppressive regimen (both P = 0.02). Conclusion Lymphopenia and high CRP levels are associated with more severe forms of COVID-19 in LT patients. Mycophenolate may have protective properties against severe COVID-19. The role of severity indicators in LT patients with COVID-19 needs to be systematically recognized.